Pemberian Daun Pepeya (Carica Papaya Linn) terhadap Kecernan Nutrisi Pakan dan Performa Ayam Joper : Determine the effect of giving papaya leaves on the digestibility of feed nutrients and the performance of Joper Chikens - Sumiati Sumiati; Syamsuhaidi Syamsuhaidi; Erwan Erwan; Dwi Kusuma Purnamasari; Vebera Maslamivera; IKG. Wiryawan; M. Wahyu (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
The research aimed at determaining the effect of giving papaya leaves on the digestibility of feed nutrients and the performance of Joper chikens has been carried out at the Teaching Farm of the Faculty of Animal Husbandry Unram Lingsar, Lingsar District, West Lombok. 100 Joper chickens aged 1 week were grouped into 5 treatment groups (P0, P1, P2, P3, P4) each group consisting of 4 replicates, each repetition consisting of 5 individuals. The feed given was CP511B and CP512B complete feed with a protein content of 18-19% and papaya leaves were given through drinking water in the form of juice. Each treatment was given papaya leaf juice as much as 5 ml/liter of drinking water (P1), 8 ml/liter of drinking water (P2), 11 ml/liter of drinking water (P3), 14ml/liter of drinking water (P4) and drinking water without papaya leaf juice ( P0) adlibitum. The variables measured were feed consumption, body weight gain, feed conversion. crude protein digestibility, crude fiber digestibility. Research data were analyzed by analysis of variance on the basis of a completely randomized design. The results of the study showed, feed consumption, body weight gain, feed conversion, crude protein digestibility, crude fiber digestibility of the five treatments was not significantly different (P>0.05). Beconcluded that determain of papaya leaf juice through drinking water up to 14 ml/liter of drinking water did not affect feed consumption, crude protein digestibility, crude fiber digestibility, body weight gain and feed conversion of Joper Chickens.